Etnocenologia da formação interdisciplinar em ciências ambientais - Lima, Márcia Fernanda de (2013)
The central object of study of this research are the senses, discursive practices and tensions experienced by students, the Graduate Program in Environment and Development, Federal University of Sergipe, on the interdisciplinary training in Environmental Sciences. Included in those who are part of MINTER UFS / UPE. It is the study of verbal interactions, face to face, in order to understand the manifestations of the spectacle of these students as interdisciplinary training of the senses and their expressions as language (non-verbal, symbolic, representational and spectacular) observed through social behaviors of actors in contexts and / or specific scenarios its manifestation. Among the major theoretical present, we focus on the contributions of Erving Goffman and his social drama. This survey was conducted between September 2011 and February 2013. Regarding methodological aspects is formed through the paradigm of etnopesquisa critical and multifaceted, with a phenomenological approach. It is a qualitative and ethnographic method was used etnocenológica base. The methodological tools used are: the systematic observation and active participant observation, intensive interviews, the autobiographical account, semidirigido questionnaire, a semistructured interview and focus group or nominal. The results of this research point to the importance of interdisciplinary training is as indispensable contribution in the professional and personal lives of the actors investigated. Also out - if the dialogues undertaken, productions and workshops as enriching this training process. However, we see that we still need an immersion in interdisciplinary, so to expand further discussions and providing an intense experience of the actors